2012
DOI: 10.1108/02621711211208925
|View full text |Cite
|
Sign up to set email alerts
|

Experiential learning for leadership and sustainability at IBM and HSBC

Abstract: Purpose -The purpose of this paper is to draw on empirical data from two major organisations (IBM and HSBC) to offer insight on the question of the effectiveness and potential value of experiential learning approaches to developing the mindsets and skills needed by organisational leaders as they respond to the pressures and opportunities of sustainability. Design/methodology/approach -The data in this paper are drawn from semi-structured interviews with previous programme participants in IBM's Corporate Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 12 publications
1
38
0
5
Order By: Relevance
“…The use of ISAs is a new trend in business practice in general (Hills and Mahmud, 2007) and in management development (Colvin, 2009;Gitsham, 2012) in particular. A growing number of companies explore ISLP as a new way of building awareness for the broader social and environmental challenges facing mankind (climate change, poverty, access to food and water, pandemics) and developing talents for dealing with the challenges of managing in a global stakeholder setting.…”
Section: Discussion and Suggestions For Further Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ISAs is a new trend in business practice in general (Hills and Mahmud, 2007) and in management development (Colvin, 2009;Gitsham, 2012) in particular. A growing number of companies explore ISLP as a new way of building awareness for the broader social and environmental challenges facing mankind (climate change, poverty, access to food and water, pandemics) and developing talents for dealing with the challenges of managing in a global stakeholder setting.…”
Section: Discussion and Suggestions For Further Researchmentioning
confidence: 99%
“…The first program was set up in 2001 by PricewaterhouseCoopers. Apart from empirical studies of this program (Pless et al, 2011(Pless et al, , 2012) and a few case study descriptions of other programs (Marquis and Kanter, 2009;Stolz et al, 2012;Gitsham, 2012), no systematic investigation of corporate programs using ISA has been undertaken. The purpose of this paper is to give an overview of various ISA-based programs, describe their characteristics (objectives, design, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interdependence of economic, environmental and social objectives at the heart of corporate sustainability requires an expansive view of the role of business in society (Bondy, Moon, and Matten, 2012;Gitsham, 2012;Quinn and Dalton, 2009). According to this view, the financial or economic imperative of business is intertwined with the inter-related challenges of: "(1) long-term viability of natural systems and the services they provide for human existence; (2) unacceptable social conditions at home and in communities around the world; and (3) the potential for local and global economies to create a modicum of wealth and prosperity for all inhabitants of the earth" (Ferdig, 2007, p.26).…”
Section: Introductionmentioning
confidence: 99%
“…Minnich (1999) indicated that one of the most important advantages of study abroad programs is that students learn-by-doing almost all day. Hence, the incorporation of ELT seems to be a logical fit for effectively teaching sustainability through study abroad programs and the benefits of incorporating ELT into teaching programs have been reported in recent studies (Gitsham, 2012;MacVaugh and Norton, 2012).…”
mentioning
confidence: 99%